BPBD Gorontalo Regency’s Flood Prevention and Mitigation Strategies: An Environmental Communication Study - Ratnasari, Dwi; Anwar, Mohamad Yudrizal; Subhan, Andi; Saputra, Ariandi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
BPBD Gorontalo Regency’s Flood Prevention and Mitigation Strategies: AnEnvironmental Communication Study. Effective communication is crucial inenhancing community awareness and preparedness for natural disasters, such asfloods. This study examines the communication strategy of the Gorontalo RegencyRegional Disaster Management Agency (BPBD) in the information disseminationabout flood disaster preparedness and mitigation to the community. It employs adescriptive-qualitative method. Data collection originates from in-depth interviews,observation, and documentation. Informant selection is conducted purposively,involving key informants, primary informants, and supporting informants. Theanalysis employs the Environmental Communication approach by Flor & Cangara,and its procedure follows the guidelines of Miles, Huberman, and Saldana. Thefindings reveal that there are several strategies carried out by the Gorontalo RegencyRegional Disaster Management Agency in the information dissemination about flooddisaster preparedness and mitigation to the community, namely: 1) CommunicationTarget Strategy, which describes that the primary communication targets are allpeople who live in the Gorontalo Regency area, specifically in flood-prone areas. Asa communicator, the Prevention and Preparedness Division of the GorontaloRegency Regional Disaster Management Agency serves as the primary source ofinformation, considering the communication targets. 2) Communication MessageStrategy, namely that each communication message has a goal that focuses on gettinginformation to the community so that the community can carry out flood disasterprevention and mitigation measures. 3) Communication Media Strategy, namely thatthe Gorontalo Regency Regional Disaster Management Agency utilizes andprioritizes social media as a tool for disseminating information in addition to othermedia, such as direct socialization or counseling. The main social media areFacebook and WhatsApp due to efficient financing and effective access. Through theinformation dissemination, the agency aims to foster a culture of resilience amongresidents.